2018
DOI: 10.1007/s00132-018-3581-0
|View full text |Cite
|
Sign up to set email alerts
|

Adult cervical deformity: radiographic and osteotomy classifications

Abstract: Cervical spine deformity represents a broad spectrum of pathologies that are both complex in etiology and debilitating towards quality of life for patients. Despite advances in the understanding of drivers and outcomes of cervical spine deformity, only one classification system and one system of nomenclature for osteotomy techniques currently exist. Moreover, there is a lack of standardization regarding the indications for each technique. This article reviews the adult cervical deformity (ACD) and current clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…In regards to deformity correction, normative values for cervical lordosis are established, however, the relationship between the restoration of alignment, HRQL, and their clinical significance remains unclear. [ 15 16 ] Similar to our study, Sabou et al . found that when used to manage fixed flexion deformities of the cervical spine in patients with ankylosing spondylitis, cervical osteotomies including pedicle subtraction osteotomies resulted in the restoration of horizontal gaze and sagittal balance as well as in improvement in HRQL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In regards to deformity correction, normative values for cervical lordosis are established, however, the relationship between the restoration of alignment, HRQL, and their clinical significance remains unclear. [ 15 16 ] Similar to our study, Sabou et al . found that when used to manage fixed flexion deformities of the cervical spine in patients with ankylosing spondylitis, cervical osteotomies including pedicle subtraction osteotomies resulted in the restoration of horizontal gaze and sagittal balance as well as in improvement in HRQL.…”
Section: Discussionsupporting
confidence: 90%
“…Management of rigid versus flexible deformity may require different treatment strategies. [ 16 19 ] Ankylosed, rigid deformities may require larger osteotomies for correction, while flexible deformities may be corrected with the anterior release with or without posterior fusion. This study found no differences in complication or reoperation rates between MAJ or MIN osteotomy patients with flexible deformities.…”
Section: Discussionmentioning
confidence: 99%
“…Deformity descriptors differentiated deformity by type, ranging from sagittal to craniovertebral junction deformities, as well as regional location factoring thoracolumbar deformities. The selected modifiers accounted for various factors correlating with ACD and thoracolumbar deformity; Diebo et al [38] described in his proposal of classification a two-step approach. Initially identifying the five most discriminate parameters are cSVA and T1 slope on lateral view, and maximum focal kyphosis, C2 slope and number of kyphotic levels on extension view.…”
Section: Classificationmentioning
confidence: 99%
“…[1][2][3] Recently, understanding of the cervical sagittal alignment and surgical methods have been developed. [3][4][5][6][7][8][9] So, surgical treatment of cervical spinal deformity (CSD) become a subject of interest. However, surgical correction of CSD can be challenging not only because it often requires osteotomies to obtain adequate correction especially in the setting of rigid CSD, but also because the target of surgical correction is adjacent to the critical neurovascular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, understanding of the cervical sagittal alignment and surgical methods have been developed [ 3 - 9 ]. So, surgical treatment of cervical spinal deformity (CSD) become a subject of interest.…”
Section: Introductionmentioning
confidence: 99%